Obtention and characterization of gluten-free baked products - Schamne, Cristiane; Dutcosky, Silvia Deboni; Demiate, Ivo Mottin (My University, 2010)
This work had as objective the development of gluten-free breads and muffins using rice flour and maize and cassava starches. From seven samples resulting from a Simplex-Centroid design, the sensory and instrumental analyses of specific volume, elasticity, and firmness were performed. For the sensory analysis, the optimized formulation contained 50% of rice flour and 50% of cassava starch, and for the instrumental evaluation, the optimal simultaneous point for the three conducted analyses were 20% of rice flour, 30% of cassava starch, and 50% of maize starch. A comparative analysis of specific volume, elasticity, firmness, and triangular test was performed with pre-baked, baked, and frozen bread. Physicochemical, nutritional, and microbiological analyses were performed for both bread and muffin according to the Brazilian legislation.

Este trabalho teve como objetivo o desenvolvimento de pães e bolos tipo muffin livres de glúten, usando farinha de arroz e amidos de milho e de mandioca. A partir de sete amostras resultantes de um delineamento Simplex-Centroide, foram realizadas análises sensoriais e instrumentais de volume específico, elasticidade e firmeza. Para a análise sensorial, a formulação ótima de mistura encontrada foi 50% de creme de arroz e 50% de amido de mandioca e, para a análise instrumental, o ponto ótimo simultâneo das três análises realizadas foi 20% de creme de arroz, 30% de amido de mandioca e 50% de amido de milho. Análises comparativas foram feitas para volume específico, elasticidade e firmeza, e teste triangular entre o pão assado e o pão pré-assado e congelado. Para ambos os produtos, foram realizadas análises físico-químicas e nutricionais, as quais estão de acordo com a legislação vigente.
Obtenção e caraterização de produtos panificados livres de glúten
Keywords: Bread; Muffin; Gluten; Celiac disease; Starch; Mixture design